Pigment patterns in adult fish result from superimposition of two largely independent pigmentation mechanisms. (22nd December 2014) - Ceinos, Rosa M.; Guillot, Raúl; Kelsh, Robert N.; Cerdá‐Reverter, José M.; Rotllant, Josep
Summary Dorso‐ventral pigment pattern differences are the most widespread pigmentary adaptations in vertebrates. In mammals, this pattern is controlled by regulating melanin chemistry in melanocytes using a protein, agouti‐signalling peptide (ASIP). In fish, studies of pigment patterning have focused on stripe formation, identifying a core striping mechanism dependent upon interactions between different pigment cell types. In contrast, mechanisms driving the dorso‐ventral countershading pattern have been overlooked. Here, we demonstrate that, in fact, zebrafish utilize two distinct adult pigment patterning mechanisms – an ancient dorso‐ventral patterning mechanism, and a more recent striping mechanism based on cell–cell interactions; remarkably, the dorso‐ventral patterning mechanism also utilizes ASIP. These two mechanisms function largely independently, with resultant patterns superimposed to give the full pattern.